Psikologi Pendidikan Dalam Meningkatkan Karakter Siswa Melalui Pembelajaran PAK - Elwira Simamora; Cecilia Simamora; Putri Hutasoit; Helena Turnip (JURNAL ILMIAH NUSANTARA, 2025)
Educational psychology plays an important role in shaping students' character through Christian Religious Education (PAK) learning. This article discusses how the application of educational psychology principles can improve students' moral, emotional, and social values. Using Piaget's cognitive development theory, Vygotsky's constructivism, and Bandura's social learning, PAK learning can be designed to support character formation more effectively. However, this implementation faces various challenges, including lack of teacher understanding, limited resources, and minimal parental involvement. To overcome these obstacles, this article recommends developing teacher competencies through training, innovation of teaching methods based on moral and spiritual values, and strengthening systemic support. Through this approach, psychology-based education can create students who are not only academically superior but also have strong moral integrity.